Recent Progress in Nanomaterial-Based Fluorescence Assays for the Detection of Food-Borne Pathogens - Shiyu Song; Lu Han; Min Chen; Leiqing Pan; Kang Tu (Sensors)
Food safety is of great concern, and food-borne bacterial infections and diseases are a major crisis for health. Therefore, it is necessary to develop rapid detection techniques for the prevention and recognition of food safety hazards caused by food-borne pathogens. In recent years, the fluorescence assay has become a widely utilized detection method due to its good signal amplification effect, high detection sensitivity, high stability, and short detection time. In this review, the different kinds of fluorescence materials were concentrated, including quantum dots (QDs), carbon dots (CDs), metal–organic frameworks (MOFs), and upconversion nanoparticles (UCNPs). The optical properties and applications of different kinds of fluorescent materials were analyzed and compared. Furthermore, according to the biosensing components, different fluorescence biosensors are reviewed, including label-free based fluorescence probes, aptamer-based biosensors, and antibody-based biosensors. Finally, we focused our attention on the discussion of fluorescent detection techniques combined with other techniques and their applications. The review presents future trends in fluorescence sensors, providing new sights for the detection of food-borne pathogens.